SME suppliers as double agents : Supplier perspective on sustainable supply chain management in the biofuel industry - Suomela, Pinja (My University, 2022)
The increasing demand and pressure for sustainable supply chain management require companies to enhance sustainability practices across entire supply chains. Studies show, however, that companies still lack the understanding of how and why small and medium-sized suppliers implement sustainable practices into their operations, and how they perceive buyer companies’ sustainability requirements and extend them to their suppliers. Existing research on the field of sustainable supply chain management has adopted the perspective of buying companies, whereas the supplier perspective especially in the context of small and medium size companies (SMEs) has received little attention, even though large buying companies’ supplier base can primarily consist of SMEs. Consequently, the purpose of this thesis is to study first-tier SME suppliers’ perceptions of buyer companies’ sustainability requirements and their double agency role in achieving sustainability across the entire supply chain. To achieve this aim, the following research questions are addressed: 1. How do first-tier SME suppliers in the biofuel industry perceive sustainability and sustainability requirements of their direct customers? 2. How do first-tier SME suppliers contribute to achieving sustainability across the entire supply chain in the biofuel industry? The study was conducted as a qualitative single case study focusing on five first-tier SME waste and residue raw material suppliers of a biofuel producer. The empirical data was collected in semi-structured theme interviews and analysed with content analysis and abductive reasoning. Findings suggest that SME suppliers adopt sustainable practices mainly due to direct customer pressure, although also other sustainability drivers were identified. In the light of the results of this study, suppliers have mainly positive attitudes towards buyer companies’ sustainability requirements. In addition, suppliers have a crucial role in achieving supply chain sustainability, and they use similar means to impose sustainability requirements on their suppliers as their buyer companies use on them. Due to the nature of the study, the empirical results provide a better understanding of phenomena but are not alleged to be widely generalizable. This study contributes to the existing theory on SME supplier-specific sustainability drivers and supply chain power, trust, and supplier sustainability development in triadic buyer–supplier–supplier relationships in the context of sustainability requirements. The study also expands previous research on first-tier suppliers’ double agency role and their perceptions of buyer companies’ sustainability requirements.

Lisääntyvät vaatimukset ja paine vastuulliselle toimitusketjujen johtamiselle edellyttää yrityksiltä koko toimitusketjun kattavaa vastuullisuutta. Tutkimukset kuitenkin osoittavat, etteivät yritykset täysin ymmärrä pienten ja keskisuurten toimittajien syitä ja keinoja toteuttaa vastuullisuutta toiminnassaan. Lisäksi ymmärrys siitä, miten toimittajat kokevat ostajayritysten vastuullisuusvaatimukset ja miten toimittajat asettavat niitä omille toimittajilleen, on vähäistä. Aiempi vastuullisen toimitusketjujen johtamisen tutkimus onkin keskittynyt pääasiassa ostajayrityksiin, kun taas pienten ja keskisuurten toimittajien näkökulma on jäänyt vähäiselle huomiolle siitäkin huolimatta, että ostajayritysten toimittajakanta koostuu usein valtaosaksi juuri tällaisista yrityksistä. Näin ollen tämän pro gradu -tutkielman tarkoituksena on tutkia pienten ja keskisuurten toimittajien näkökulmaa ostajayritysten vastuullisuusvaatimuksiin, ja näiden kaksoisagentin roolia koko toimitusketjun kattavan vastuullisuuden saavuttamisessa. Aihetta lähestytään seuraavien tutkimuskysymysten kautta: 1. Miten ensimmäisen tason pienet ja keskisuuret toimittajat biopolttoaineteollisuudessa kokevat vastuullisuuden ja suorien asiakkaiden vastuullisuusvaatimukset? 2. Miten ensimmäisen tason pienet ja keskisuuret toimittajat biopolttoaineteollisuudessa myötävaikuttavat koko toimitusketjun kattavan vastuullisuuden saavuttamiseen? Tutkimus toteutettiin kvalitatiivisina yksittäisenä tapaustutkimuksena, jossa analyysiyksikkönä oli tietyn biodieselvalmistajan viisi jätteiden ja tähteiden toimittajaa. Empiirinen data kerättiin puolistrukturoituina teemahaastatteluina ja data analysoitiin sisällönanalyysillä abduktiivista päättelyä hyödyntäen. Tutkielma antoi hyödyllistä tietoa vastuullisesta toimitusketjujen johtamisesta ensimmäisen tason toimittajien näkökulmasta. Tulokset viittaavat siihen, että toimittajat toteuttavat vastuullisuutta erityisesti ostajayritysten vaatimusten vuoksi. Toimittajat kuitenkin suhtautuvat näihin vaatimuksiin neutraalisti tai positiivisesti. Tutkielma osoitti, että ensimmäisen tason toimittajilla on kriittinen rooli toimitusketjun vastuullisuuden saavuttamisessa, ja toimittajat käyttävät saman tyyppisiä keinoja vastuullisuusvaatimusten asettamiseen kuin ostajayrityksetkin. Tutkimustulokset laajentavat ymmärrystä tutkittavasta ilmiöstä, mutta ne eivät ole laajasti yleistettävissä tutkielman luonteesta johtuen. Tutkielma täydentää olemassa olevaa teoriaa toimittajien vastuullisuusajureista, ja vallasta, luottamuksesta ja toimittajien vastuullisuuden kehittämisestä kolminaisissa ostaja–toimittaja–toimittajasuhteissa vastuullisuusvaatimusten kontekstissa. Tutkielma laajentaa myös ensimmäisen tason toimittajien kaksoisagenttirooliin liittyvää teoriaa ja ymmärrystä näiden näkemyksistä ostajayritysten vastuullisuusvaatimuksiin. Tulokset voivat olla hyödyllisiä myös toimitusketjujen ammattilaisille, joiden tavoitteena on parantaa koko toimitusketjun kattavaa vastuullisuutta. Tutkielman tulosten perusteella voidaan tehdä useita ehdotuksia jatkotutkimuksia ajatellen.
Keywords: Sustainable supply chain management, sustainability requirements, supply chain power, sustainable supplier development, trust, supply chain relationships, SMEs